1994
DOI: 10.1063/1.112980
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal oxidation of silicon in N2O between 800 and 1200 °C: Incorporated nitrogen and interfacial roughness

Abstract: Oxynitrides can suppress the diffusion of boron from the polycrystalline silicon gate electrode to the channel region of an ultralarge scale integrated device, and are therefore important potential substrates for thin SiO2 gates. Direct oxynitridation of Si in N2O is a simple and manufacturable N incorporation scheme. We have used rapid thermal oxidation to grow O2- and N2O-oxides of technological importance (∼10 nm thick) in the temperature range 800–1200 °C. Accurate measurements of the N content of the N2O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…It was further found with X-ray photoelectron spectroscopy (XPS) that the total nitrogen surface concentration of the prepared ''oxynitride'' is about (3 ± 1) · 10 14 cm À2 . This amount is close to the surface density of a half monolayer of solid and is close to the values of other reports [108][109][110][111][112]. The distribution of nitrogen atoms are mainly found at the Si/dielectric interface and it was believed that the nitrogen incorporation is made mainly via the chemical reaction with the interface Si-Si bonds [105,111], i.e.…”
Section: The Prospect and Process Variantssupporting
confidence: 83%
“…It was further found with X-ray photoelectron spectroscopy (XPS) that the total nitrogen surface concentration of the prepared ''oxynitride'' is about (3 ± 1) · 10 14 cm À2 . This amount is close to the surface density of a half monolayer of solid and is close to the values of other reports [108][109][110][111][112]. The distribution of nitrogen atoms are mainly found at the Si/dielectric interface and it was believed that the nitrogen incorporation is made mainly via the chemical reaction with the interface Si-Si bonds [105,111], i.e.…”
Section: The Prospect and Process Variantssupporting
confidence: 83%
“…Two approaches have been used, secondary ion mass spectroscopy ͑SIMS͒ 2,5,9,12 and HF etch-back methods 3,13,14 In addition to the limited depth resolution of these methods, SIMS analysis is complicated by matrix effects, while HF etching may introduce nonuniform oxide removal ͑especially in the presence of nitrogen-rich regions͒.…”
mentioning
confidence: 99%
“…In addition, N atom incorporation at the SiO 2 /Si interface can stabilize the SiO 2 /Si interface. 3 Electrical performance measurements on MOS capacitor and field effect transistor (FET) also confirmed that the N atoms enhanced both defect densities at the interface as well as reliability. 4 It was also demonstrated that the oxynitride gate dielectrics had a number of properties superior to conventional oxides, such as lower leakage current and improved electrical stress properties.…”
Section: Introductionmentioning
confidence: 67%